From Textbooks to Beyond Textbooks in English Class: An Action Research Study - Pokhrel, Vidhya (Journal of Transformative Praxis, 2022)
This paper explores the meaningfulness of going beyond textbooks in the English classroom. It aims at exploring the limitations of a textbook as well as the relevance of going beyond textbooks along with learners’ achievements which covers the wide range of the academic pursuit through meaningful action of going beyond textbooks. Further, the paper gives the scenario of how I identified the problem, developed the action plan and implemented those plans in the English class. The research has been guided by the Frierian notion of freedom of practice and engagement theory, where engagement implies an effort that one puts attempt to achieve goals and encourages learners for pleasurable participation, which has been presented in this research by bringing the real classroom scenario. The fear of freedom while keeping them bound to the textbook and the practice of freedom while taking them beyond the textbook has been revealed through action research with the intervention of action plans that were developed such as engaging students in newspaper-related activities, watching movies, and doing collaborative work where students learned the English language with much enjoyment going beyond the textbook. Overall, the developed paper is anticipated to the transformative potential of the ‘beyond textbooks’ concept and to extend the mindfulness upon the curriculum designers and teachers who can think of including activities beyond textbooks in English curriculum and classroom activities, respectively.